2007
DOI: 10.1149/1.2435511
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Cycle Performance of a High-Voltage Hybrid Electrochemical Capacitor

Abstract: A technology for preventing capacity loss during charge-discharge cycling of a high-voltage hybrid electrochemical capacitor is presented. During high-voltage cycling of the capacitor, which combined the negative electrode of a lithium-ion battery with the positive electrode of an electric double-layer capacitor, extreme capacity loss occurred through a decline in the capacity of the negative electrode when the positive electrode was highly polarized ͑at over 4 V vs Li/Li + ͒. A method of preventing this capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…111 It was also reported that capacity loss of the LICs during charge-discharge cycling was obviously reduced by addition of Li metal into the cell. 112,113 The highest potential of the AC electrode should be lower than 4.5 V vs Li + /Li, while the lowest potential of the HC/stabilized Li metal powder (SLMP) electrode should be greater than 0.1 V vs. Li + /Li. Moreover, the capacitance degradation of this LIC was less than 1 % after 1300 cycles in a voltage range of 2.0 to 4.1 V. 114 Please do not adjust margins Please do not adjust margins Additionally, it was proposed to use quaternary alkyl ammonium and PC based organic electrolytes in LICs.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…111 It was also reported that capacity loss of the LICs during charge-discharge cycling was obviously reduced by addition of Li metal into the cell. 112,113 The highest potential of the AC electrode should be lower than 4.5 V vs Li + /Li, while the lowest potential of the HC/stabilized Li metal powder (SLMP) electrode should be greater than 0.1 V vs. Li + /Li. Moreover, the capacitance degradation of this LIC was less than 1 % after 1300 cycles in a voltage range of 2.0 to 4.1 V. 114 Please do not adjust margins Please do not adjust margins Additionally, it was proposed to use quaternary alkyl ammonium and PC based organic electrolytes in LICs.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…The coulombic efficiency at a pre-lithiation of 7.5% was not high ($95%) and showed a moderate decrease. The absence of pre-lithiation resulted in the lowest coulombic efficiency (85% in cycles 1-5 and 20% in cycles [20][21][22][23][24][25].…”
Section: Cycle Performance Of Lic Cellsmentioning
confidence: 99%
“…This excellent property can alleviate electrolyte decomposition resulting from the increased redox potential (>4.5 V vs. Li/Li + ) at the PE [18,19]. The process of pre-lithiation or Li pre-doping is essential to provide graphite with a low redox potential, thus elevating the working voltage of the cell, which is typically 2.0-4.0 V. The potential swing at the graphite NE during Li intercalationdeintercalation can affect the capacitance and the cycle stability of the cells [19,20]. Zhang et al have studied the effect of the degree of pre-lithiation of graphite-type NEs (mesocarbon microbeads, MCMBs) on the electrochemical performance of LICs [21].…”
Section: Introductionmentioning
confidence: 99%
“…The common approach which has been recently introduced for realizing asymmetric capacitors using any of these two materials, as negative electrode combined with an activated carbon, consists in extending the working potential window of the positive electrode [113][114][115][116]. In this sense, Figure 8.32 shows a scheme of the potential profi les during charging two different asymmetric confi gurations (Figure 8.32a) and a symmetric double-layer capacitor (Figure 8.32b) [114].…”
Section: New Asymmetric Systems Working In Organic Electrolytesmentioning
confidence: 99%